Campaña publicitaria de difusión y promoción de los destinos turísticos del Cantón La Maná, en el año 2018 - Chalco Villa, Manuel Jesús (2018)
The objective of this study has been to develop a proposal for an advertising campaign for the development of the Canton La Mana Province of Cotopaxi. This campaign allows people to visit the places they have to offer tourists and at the same time inform other people about their experience and generate enthusiasm for the futures visitors. For which a multimedia has been presented in order to obtain more attention from teenagers and young people, who make the decision to visit new places on next vacation. The proposal allows an easy and intuitive way to know the place by means of images, videos, and tourist information materials. The campaign has been done in the Adobe software and also in Dreamweaver. In order to achieve the research objectives, different activities and techniques were carried out, among which they emphasize, to know the exigencies of the tourists and application of a data collection instrument. Keywords: Advertising, information, Media, GAD Municipal la Mana, Creativity Culture, Message, Receiver, Idea